Description of The Effect of The Covid-19 Pandemic on The Sleep of Yarsi University Medical Students Class of 2020 and 2021 and It's Review from Islamic Perspective - Data Erdian Mahendra; Samsul Mustofa (Junior Medical Journal, 2023)
The current Covid-19 pandemic causes psychosocial problems such as stress, worry, anxiety, depressive symptoms, and sleep disturbances. College students are one of the populations affected by this pandemic. In recent months, students have changed their routine due to the COVID-19 pandemic allowing students to adjust their study hours as they no longer have to attend the usual morning classes in the classroom. All of these changes to learning systems and schedules are additional factors in sleep problems, and affect performance. The purpose of this study was to describe the influence of the Covid-19 pandemic on sleep patterns of Yarsi University Medical Students Batch 2020 and 2021. The type of research that will be used in this study is an analytical survey research. The population in this study were all students of the Faculty of Medicine, YARSI University, class of 2020, totaling 211 students and class of 2021, totaling 146 students. This study used univariate and bivariate analysis methods. The results of the study show that students affected by the COVID-19 pandemic have poor sleep patterns. In the Islamic view, sleep can restore energy, with regular sleep patterns and good quality sleep will affect the health of the body. This shows that according to Islamic rules sleep is an important activity for humans to keep the body healthy